Pengaruh Promosi, Preferensi Merek, dan Keragaman Produk Terhadap Keputusan Pembelian Makanan Beku - Putri, Inez Amanda; Ali, Ali (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of promotion, brand preference, and product diversity on consumer purchasing decisions at Frozen Food Store. The background of this research stems from the increasing competition in the frozen food industry, which requires businesses to understand the factors that influence consumer behavior in making purchasing decisions. A quantitative approach was used, with data collected through questionnaires distributed to 103 respondents who are active consumers of the Frozen Food Store. Data were analyzed using multiple linear regression to determine the effect of each independent variable on the dependent variable. The results show that promotion and brand preference have a positive and significant influence on purchasing decisions, while product diversity does not show a significant effect. These findings imply that marketing strategies focused on improving promotional quality and strengthening brand image can enhance consumer purchasing decisions. This research is expected to contribute to the development of marketing knowledge and serve as a practical reference for business practitioners in the frozen food sector in formulating more effective strategies.